Pengaruh Metode Edutainment terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS - Safa Amaliatus Sa’adah; Aris Aris; Ratna Puspitasari (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2022)
Studying history in social studies subjects for most students is boring, this is because according to them there is a lack or lack of variety of learning methods that can attract students' interest in studying history. For most students, the method used by the teacher is only lectures. So it makes students bored. This study analyzes the impact of using the edutainment method as the application of the method in history learning. This method focuses on the end result of the learning process. Thus, this study aims to see how much influence the use of edutainment methods has on students in history material. This research method uses a quantitative type, with data collection in the form of student learning outcomes data, such as questionnaires and student opinions. Meanwhile, the research population was students of class VIII B and VIII D MTs Al-Hilal Tegalgubug. The results of this study include the results of descriptive statistical analysis, the average value of students on historical material with the edutainment method is 86.43. In testing the response to the use of the edutainment method, it shows a good number, namely 82%. Based on these two opportunities, it can be concluded that the edutainment method is effective in improving the history learning outcomes of class VIII B and D students of MTs Al-Hillal Tegalgubug Arjawinangun. The conclusion of this research is that there is a significant effect between the application of the edutainment method on student learning outcomes. Keywords: Edutainment method, social studies learning, history learning